Being Malaysian: The Role and Challenges of Citizenship Education - Aziz, Nur Atiqah Tang Abdullah; Nurazimah Binti (Journal of Ecohumanism, 2024)
Citizenship Education in Malaysia is a product of social fragmentation that carries legal and sociological meanings. This paper aims to pull together citizenship and education as central themes, not legal but the sociological aspects, with ‘nation-of-intent’ as a conceptual framework. However, the present effort of citizenship education in Malaysia is based on a particular form of ‘nation-of-intent’ (‘Bangsa’ Malaysia). The concept of citizenship and citizenship education in Malaysia is prompting only one form of ‘nation-of intent’ available in the country, whereas there are other nations as well, apparently. The presence of plurality of ‘nation-of-intent’ in contemporary Malaysia demonstrates the fact that dissenting voices are present and heard, within and without government. Therefore, in the context of different ‘nation-of-intent’s which exist, there is a need to explore and clarify what being ‘Malaysian’ means in its true context.